2008
DOI: 10.1002/iroh.200710959
|View full text |Cite
|
Sign up to set email alerts
|

The Stream Inlet to a Shallow Bay of a Drinking Water Reservoir, a ‘Hot‐Spot’ for Microcystis Blooms Initiation

Abstract: Stream inlets into shallow bays of reservoirs and lakes may be 'hot-spots' for toxic cyanobacterial bloom initiation. These 'hot-spots' may be connected with the permanent inflow of high nutrient concentrations from the catchment, optimal physical conditions (wind protected areas) that occur in shallow areas and/or ineffective top-down control. Four sampling sites along a transect from stream to reservoir in a shallow bay of Sulejow Reservoir (Poland) were studied to test the above hypothesis, comprising a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…It is a typical lowland shallow reservoir, with an area of approximately 2700 ha, an average depth of 3.3 m and a max depth of 11 m. The reservoir is eutrophic, and the chlorophyll a concentration during growth seasons reaches a mean value of 30 g dm −3 and can exceed 150 g dm −3 during phytoplankton blooms. The dominant species of cyanobacteria in the area is Microcystis aeruginosa (Wagner and Zalewski 2000;Izydorczyk et al, 2008b). The analysis of cyanobacterial bloom samples confirmed their highly hepatotoxic character (Tarczyńska et al, 2001;Jurczak et al, 2004;Mankiewicz-Boczek et al, 2006a,b;Izydorczyk et al, 2008a;Gągała et al, 2013).…”
Section: Study Areamentioning
confidence: 59%
See 1 more Smart Citation
“…It is a typical lowland shallow reservoir, with an area of approximately 2700 ha, an average depth of 3.3 m and a max depth of 11 m. The reservoir is eutrophic, and the chlorophyll a concentration during growth seasons reaches a mean value of 30 g dm −3 and can exceed 150 g dm −3 during phytoplankton blooms. The dominant species of cyanobacteria in the area is Microcystis aeruginosa (Wagner and Zalewski 2000;Izydorczyk et al, 2008b). The analysis of cyanobacterial bloom samples confirmed their highly hepatotoxic character (Tarczyńska et al, 2001;Jurczak et al, 2004;Mankiewicz-Boczek et al, 2006a,b;Izydorczyk et al, 2008a;Gągała et al, 2013).…”
Section: Study Areamentioning
confidence: 59%
“…In the past decades, increasing eutrophication has led to frequent outbreaks of cyanobacterial blooms in many lakes and reservoirs all over the world (Dokulil and Teubner 2000;Tarczyńska et al, 2001;Anderson et al, 2002;Briand et al, 2003;Chorus 2005;Mankiewicz-Boczek et al, 2006a;Xie et al, 2007;Izydorczyk et al, 2008aIzydorczyk et al, , 2008bGągała et al, 2010). The probability of cyanobacterial toxic blooms will likely increase in the next several decades due to the consequences of climate change on freshwater ecosystems, which will pose potential risks to fish ecology and ecosystem sustainability (Paerl and Huisman 2008;Jöhnk et al, 2008;Wagner and Adrian 2009;Huber et al, 2012;Kosten et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This is partly because embayments are usually shallow and sheltered from the main channel of lakes or reservoirs. Hence, embayments often experience low flushing or longer water residence time (Mitrovic et al 2001;Hall et al 2003;Izydorczyk et al 2008). Consequently, the combined effects of nutrients released from anthropogenic activities in embayments and their longer residence time may encourage rapid algal growth and nuisance algal blooms (Izydorczyk et al 2008;Poste et al 2012;Mbonde et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, embayments often experience low flushing or longer water residence time (Mitrovic et al 2001;Hall et al 2003;Izydorczyk et al 2008). Consequently, the combined effects of nutrients released from anthropogenic activities in embayments and their longer residence time may encourage rapid algal growth and nuisance algal blooms (Izydorczyk et al 2008;Poste et al 2012;Mbonde et al 2015). For instance, Hall et al (2003) found that higher total phosphorus (TP) concentrations were associated with greater chlorophyll a concentrations in three embayments (Sodus Bay, Sandy Pond and Chaumont Bay) compared to offshore locations in Lake Ontario, Canada.…”
Section: Introductionmentioning
confidence: 99%
“…This area is characterized by stable hydrological conditions, with retention times of up to 60 days, and a high supply of nutrients from the catchment area, which favors cyanobacterial growth, mainly Microcystis aeruginosa Kütz. and Aphanizomenon flos-aquae (L.) (Izydorczyk et al, 2008). The dominant species of bloom-forming cyanobacteria is M. aeruginosa, which produces microcystin-LR (MC-LR), microcystin-YR (MC-YR) and MC-RR (Jurczak et al, 2005;Gągała et al, 2014 (Frankiewicz et al, 1999;Frankiewicz and Świerzowski, 2004).…”
Section: Sulejow Reservoirmentioning
confidence: 99%